GEOGRAPHY OF SPORTS: THEORETICAL AND METHODOLOGICAL APPROACHES TO THE FORMATION OF A SCIENTIFIC DIRECTION - I. P. Suprunchuk (Наука. Инновации. Технологии, 2022)
Introduction. One of the new directions in socio-economic geography is the geography of sports. In Russian geographical science, its development is at an early stage. At the same time, sport is an important aspect of economic, social and political life, and the geography of sports as a spatial science can provide a lot of fundamental and applied data in this sphere. Materials and methods of the research. The method of literary review is used in relation to modern geographical research of sports. Sport is presented as a complex object studied by many scientific directions. With the help of the analytical method, a research scheme has been developed for the selected areas of the geography of sports. The results of the research and their discussion. The conducted literature review showed the small number and under-development of geographical research in the field of sports. In Russian geography, sports were practically not considered until recently. The system of sciences studying sports is considered, the place of geography in it and its potential possibilities are determined. The directions of the development of the geography of sports and their potential tools are proposed. Conclusions. Sport is a complex of interrelated processes and spheres, and is the object of study of many sciences. In geographical science, attempts have been made to study sports geographically. At the same time, there was no formation of a separate scientific direction. Geography of sports is a scientiic direction in socio-economic geography that studies the territorial organization of sports.